Influence of Display Luminance on Visual Discomfort in Dark Ambient Based on Haemodynamic Response - Yunyang Shi; Yan Tu; Lili Wang; Yin Zhang; Xin Gao (IEEE Photonics Journal)
Display luminance is one of the most important factors that influence not only display performance but also visual discomfort greatly. To investigate the influence of display luminance and image content on visual discomfort, the haemodynamic response and subjective perception were recorded respectively when participants watched different visual stimuli. Different white levels (WLs) of display and images with different spatial amplitude spectra were adopted as the visual stimuli, and specific dark environment was applied in the study. The results showed that under dark ambient condition, the WL had significant influences on visual discomfort, which varied in images with different spatial amplitude spectra. The findings also indicated that, for visual discomfort measurement, the sensitivity of haemodynamic response was better than subjective evaluation.